2022
DOI: 10.1039/d2nj01702d
|View full text |Cite
|
Sign up to set email alerts
|

Revealing initial nucleation of hexagonal boron nitride on Ru(0001) and Rh(111) surfaces by density functional theory simulations

Abstract: The nucleation of h-BN on Ru(0001) and Rh(111) surfaces via an energy-driven process is systematically studied by density functional theory simulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It has been found that the most stable hBN over Ru(0001) configuration occurs when boron atoms continue the hcp stacking arrangement and nitrogen atoms sit on the adjacent top site directly above the Ru in the layer below. [71][72][73] Charge transfer between hBN and Ru(0001) leads to repulsive/attractive forces acting on the nitrogen/boron of the hBN overlayer. 73 Consequently, the boron atoms are marginally closer to the surface than the nitrogen.…”
Section: Ammonia Decomposition On Hbn/ru(0001)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that the most stable hBN over Ru(0001) configuration occurs when boron atoms continue the hcp stacking arrangement and nitrogen atoms sit on the adjacent top site directly above the Ru in the layer below. [71][72][73] Charge transfer between hBN and Ru(0001) leads to repulsive/attractive forces acting on the nitrogen/boron of the hBN overlayer. 73 Consequently, the boron atoms are marginally closer to the surface than the nitrogen.…”
Section: Ammonia Decomposition On Hbn/ru(0001)mentioning
confidence: 99%
“…[71][72][73] Charge transfer between hBN and Ru(0001) leads to repulsive/attractive forces acting on the nitrogen/boron of the hBN overlayer. 73 Consequently, the boron atoms are marginally closer to the surface than the nitrogen. It is important to note that larger cells of hBN/Ru(0001) lead to the formation of a 12 Â 12 nanomesh, however, experimentally the nanomesh consists of large pores 2.2 Å above the Ru(0001) surface, 71 a similar distance to our calculated value of 2.17 Å and where vacancies would have adequate space to form.…”
Section: Ammonia Decomposition On Hbn/ru(0001)mentioning
confidence: 99%
“…24 In addition to the great efforts of experimental scientists, theoretical scientists have also made extensive explorations to reveal the growth mechanism of h-BN. Recently, Zhao and co-workers reported the nucleation of h-BN on Rh(111), 42 Ru(0001), 43 Ni(100), 44 and Ni(111) 45 surfaces and revealed the crossover from 1D chains to the sp 2 hybrid 2D network in the early stage of h-BN growth.…”
Section: Introductionmentioning
confidence: 99%
“…Since the successful exfoliation of graphene in 2004, twodimensional (2D) materials have attracted great attention due to their intriguing electronic properties. [1][2][3][4] Among various 2D materials, 5,6 transition-metal dichalcogenides (TMDs) exhibit various promising applications in many fields, including optoelectronic devices, 7 gas sensing materials 8 and electronic devices. 9 Unfortunately, the electrical properties of TMDs present a high dependence on the number of layers, 10 strain 11 and bandwidth, 12 which greatly inhibits their applications.…”
Section: Introductionmentioning
confidence: 99%